VASPIN, ADIPONECTIN AND LEPTIN LEVELS IN TYPE 1 DIABETIC RATS INDUCED BY STREPTOZOTOCIN - ELÇİOĞLU, HATİCE KÜBRA (EDITURA ACAD ROMANE, 2020)
Background. Adiponectin, vaspin and leptin are only a few of these numerous adipocytokines. Little is known about the behavior of adipocytokines and how adipose tissue metabolism is affected in this Type 1 DM model. In this study we investigated the serum levels of adiponectin, leptin, vaspin in streptozotocin(STZ) induced diabetic rats. Material and methods. Twelve Sprague Dawley albino rats were included in the study. The animals were divided into two groups. The first group was diabetic (D) (n: 6) and 60mg / kg STZ was administered intraperitoneally (i.p.) to these rats. The second group was the non-diabetic control (ND) group (n: 6). All the animals were euthanized by cervical dislocation. Quantification of vaspin, Adiponectin, leptin in serum was performed using the ELISA kit. Results. Adiponectin, vaspin levels of diabetic group were found to be statistically lower than of control group (p<0.05). Leptin levels were significantly higher in the diabetic group (P<0.05). Conclusion. There is a need for new researches that can explain the relationship between Vaspin, Leptin and Adiponectin and Type 1 diabetes. New studies in this area will open new horizons for the identification of new biomarkers in the diagnosis and treatment of Type 1 diabetes.
Keywords: Vaspin; Adiponectin; Leptin; Type 1 diabetes; Streptozotocin; SERINE-PROTEASE INHIBITOR; INSULIN-RESISTANCE; FAT; ADIPOCYTOKINE; ADIPOSITY; INJURY; ALPHA; LIVER